A Simulation Approach Including Underresolved Scales for Two-Component Fluid Flows in Multiscale Porous Structures (Communications in Computational Physics, 2023)
In this study, we develop computational models and a methodology foraccurate multicomponent flow simulation in underresolved multiscale porous structures [1]. It is generally impractical to fully resolve the flow in porous structureswith large length-scale differences due to the tremendously high computational expense. The flow contributions from underresolved scales should be taken into accountwith proper physics modeling and simulation processes. Using precomputed physical properties such as the absolute permeability, $K_0,$ the capillary pressure-saturationcurve, and the relative permeability, $K_r,$ in typical resolved porous structures, the local fluid force is determined and applied to simulations in the underresolved regions,which are represented by porous media. In this way, accurate flow simulations inmultiscale porous structures become feasible.To evaluate the accuracy and robustness of this method, a set of benchmark test casesare simulated for both single-component and two-component flows in artificially constructed multiscale porous structures. Using comparisons with analytic solutions andresults with much finer resolution resolving the porous structures, the simulated results are examined. Indeed, in all cases, the results successfully show high accuracywith proper input of $K_0,$ capillary pressure, and $K_r.$ Specifically, imbibition patterns,entry pressure, residual component patterns, and absolute/relative permeability areaccurately captured with this approach.
Keywords: Multiscale simulation; porous media; multicomponent flow; lattice Boltzmann method.